La Colombie-Britannique : domicile de compagnies captives depuis 1987 - Moreau, Rémi (Assurances)

(untitled) (HEC Montréal, 1989)
A Captive Insurance Company is an insurance company formed by an organization or organizations (which operate mainly outside of the insurance business) to handle all or part of the insurance needs of the owners (Foresight). The author discusses the main aspects of the British Columbia Insurance (Captive Company) Act: costs, capitalization, taxation and governmental control. The reader will also find pertinent comparative information on other North American captive laws. In his conclusion, he presents certain advantages relating to the setting up of a captive in British Columbia.